The ancient novel and beyond - Panayotakis, Stelios, 1968-; Zimmerman, M. (Maaike); Keulen, Wytse Hette (Mnemosyne, bibliotheca classica Batava. Supplementum, 2003)
This work comprises the revised versions of selected papers read at the International Conference on the Ancient Novel (Groningen, July 2000). The essays combine judicious use of literary theory with traditional scholarship, and examines the ancient novels and related texts.